Riometer Records of 30 MHz Cosmic Noise at Syowa Station, Antarctica from February 1967 to February 1968 - オセ, マサミ; ニシムタ, イチゾウ; OSE, Masami; NISHIMUTA, Ichizo (National Institute of Polar Research, 1968)
P(論文) departmental bulletin paper